Tinjauan Yuridis atas Hak Tanggungan yang dilaksanakan secara Elektronik - Chariss Wong, Shervira; Teo Pan, Nicholas; Fernandez, Lucky (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Mortgage rights are collateral rights that encumber a land right to pay off certain debts, since the promulgation and enactment of Ministerial Regulation of ATR/Head of BPN No. 5 of 2020 concerning Electronically Integrated Mortgage Services. Mortgage services are carried out through a system called the HT-el system, where the HT-el system can speed up and simplify the implementation of the Mortgage. This article aims to add insight and provide information on how to arrange Mortgage, namely Electronic Mortgage which is carried out through the HT-el System. This article uses the Normative Juridical Research Method. The results show that the implementation practice of the Mortgage Rights has been implemented properly and evenly, is more effective than its predecessors and only encounters obstacles in the telecommunications network.